PHRASEOLOGY - A WAY OF KNOWING A PERSON - Temirova Shoira Gaibullaevna; Tuychieva Dilafruz; Ochilovа Nasiba Nematovna (American Journals, 2023)
This scientific article is devoted to the study of phraseological equivalents in Russian and Uzbek languages and examines phraseological units and phraseological turns. Their classification and definitions are considered.
Keywords: Phraseological turns, lexical, semantic, expressiveness, vocabulary, сarelessly, phraseological turnover, stable figurative expressions.